Regulation of the Prohibition of the Use of Human Drug in the Veterinary Field - Christabella Gunawan (Budapest International Research and Critics University, 2022)
Veterinary is one of the fields of medical science whose treatment targets are animals. Veterinary medicine is often underestimated because the focus of this type of treatment, psychological analysis, prevention and surgery is only for the animal world. Herbal medicine, both herbal medicine and traditional medicine for generations, is a treatment that was used before veterinary science took over in various treatments for livestock or pets. But when herbal medicine and traditional ingredients cannot provide a solution to various critical diseases in animals, then the use of human medicine becomes an alternative. When humans think that when they are sick they are given one of the drugs for example drug A (medicine for humans) and recover, then the same is true for animals. The lack of veterinary personnel in Indonesia is often the reason for the use of these human drugs. There must be a cure if it is true that human medicine is used for animals, but if consumption of livestock such as cows, goats, fish, etc. are continuously given human antibiotics, it will have a negative impact which will give rise to super bacteria that are resistant to antibiotics. Structuring the laws governing the prohibition of the use of human drugs for the veterinary sector is very important because veterinarians in various regions often use human drugs if no drugs are found to treat the disease in the animal. Arrangements are also needed to regulate veterinary pharmacies which are currently attracting the attention of various groups which will clash with pet shops or poultry shops which also provide various kinds of veterinary medicines.